Headhunters on my doorstep : a true treasure island ghost story - Troost, J. Maarten (Gotham, 2013)
This book chronicles the author's return to the South Pacific after his struggle with alcoholism and time in rehab left him numb to life. He is now married to his sweetheart and father of two young boys. Deciding to retrace the path once traveled by the author of Treasure Island, he follows Robert Louis Stevenson to the Marquesas, the Tuamotus, Tahiti, the Gilberts, and Samoa, tumbling from one comic misadventure to another as he confronts his newfound sobriety. Somewhere en route from the shark-infested waters of Fakarava to the remote islands of Kiribati, he gradually awakens to the beauty of life, managing an honest look at addiction and human nature, without self-pity and without ever losing his sense of humor. He is able to reconnect with his family and the world. This is a funny yet poignant account of one man's journey to find himself.